Strong control of effective radiative forcing by the spatial pattern of absorbing aerosol - Williams, AIL; Stier, P; Dagan, G; Watson-Parris, D (Springer Nature, 2022)
Over the coming decades, it is expected that the spatial pattern of anthropogenic aerosol will change dramatically and the global aerosol composition will become relatively more absorbing. Yet, the climatic impact of this evolving spatial pattern of absorbing aerosol has received relatively little attention, in particular its impact on global-mean effective radiative forcing. Here, using model experiments, we show that the effective radiative forcing from absorbing aerosol varies strongly depending on their location, driven by rapid adjustments of clouds and circulation. Our experiments generate positive effective radiative forcing in response to aerosol absorption throughout the midlatitudes and most of the tropical regions, and a strong ‘hot spot’ of negative effective radiative forcing in response to aerosol absorption over the tropical Western Pacific. Further, these diverse responses can be robustly attributed to changes in atmospheric dynamics and highlight the importance of this ‘aerosol pattern effect’ for transient forcing from regional biomass-burning aerosol.